Undergraduates' preference to becoming an entrepreneur / Falex J. Langkan, Cyril Supain @ Christopher and Rozita @ Uji Mohammed - Langkan, Falex; Supain @ Christopher, Cyrill; Mohammed, Rozita @ Uji (2018)
The increasing rate of unemployed undergraduates is one of the issues that has triggered the world's concern lately. The number of undergraduates turned out every year from higher learning institutions is more than what the labour market can absorb. As stated by the Department of Statistics Malaysia, a 2016 report estimated that there were at least 200,000 unemployed graduates in Malaysia and that number was predicted to rise. It is also stated that the national unemployment was 3.5% out of 14 million Malaysians in the labour market. High unemployment rates has turned the labour market to force many undergraduates to look at their own skills and resourcefulness in order to create income opportunities hence turning them into becoming an entrepreneur. An entrepreneur is an individual who introduces some ideas or adding value in existing ideas and products. This preliminary research will focus on undergraduates which are believed by many scholars can be trained to become real entrepreneurs. The study of undergraduates' preference in becoming an entrepreneur has led to the identification of possible determinants. Out of all the determinants, this research will identify the most significant factor contributing towards undergraduates' preference to become an entrepreneur. This study will involve 121 students in a Malaysian public university specifically in Universiti Teknologi MARA (UiTM) Sabah Branch.